The noise performance of CMOS Miller operational transconductance amplifiers with embedded current‐buffer frequency compensation. (29th September 2016) - Grasso, Alfio Dario; Palumbo, Gaetano; Pennisi, Salvatore; Sansen, Willy
Summary: The noise of cascode transistors is usually considered to be negligible. It is demonstrated in this paper that this is not the case for an operational transconductance amplifiers exploiting Miller compensation via an embedded current buffer. Analysis, validated through simulations, shows that the noise power spectral density of the cascode transistor implementing the buffer, can be dominant at high frequencies. Its contribution can be of the same order of magnitude as that of the transistors in the first gain stage. A design equation is also given to limit the increase of this output noise contribution. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : The noise of cascode transistors is usually considered to be negligible. It is demonstrated in this paper that this is not the case for an operational transconductance amplifiers exploiting Miller compensation via an embedded current buffer. It is shown analytically and by means of simulations that the noise power spectral density of the cascode transistor implementing the current buffer (M6) can be dominant at high frequencies. Its contribution can be of the same order of magnitude as that of the transistors in the first gain stage. This has been found to be the case for frequencies just below the gain‐bandwidth product. A simple design equation was found to reduce this effect.